(untitled) (International relations and international law Journal, 2016)
The article is devoted to the Iranian nuclear program – one of ongoing problems in international relations.Kazakhstanhas established itself on the world stage as an active participant in solving the problems of nuclear safety. In this article authors analyze the role of Kazakhstani position in resolving the Iranian nuclear issue. The authors make an overview of achievements of Kazakhstan in the field of nuclear safety, as well as considering the bilateral relations of Kazakhstan and Iran. Determining the position of Kazakhstan in relation to Iran’s nuclear program, the authors also consider the contribution of Kazakhstan in the resolving this issue. In addition, authors analyze current situation over the Iranian nuclear issue, and examine in detail the historically significant Interim Agreement on the Iranian nuclear program